2013
DOI: 10.4161/epi.23605
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-mediated transcriptional repression of microRNAs during cervical carcinogenesis

Abstract: Deregulated expression of microRNAs (miRNAs) is common and biologically relevant in cervical carcinogenesis and appears only partly related to chromosomal changes. We recently identified 32 miRNAs showing decreased expression in high-grade cervical intraepithelial neoplasia (CIN) and carcinomas not associated with a chromosomal loss, 6 of which were located within a CpG island. This study aimed to investigate to what extent these miRNAs are subject to DNA methylation-mediated transcriptional repression in cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 37 publications
7
70
0
Order By: Relevance
“…Recently, hypermethylation of miR-203 promoter has been found in HCC, cervical cancer and CML [12,13,17,32]. In this study, we confirmed that the mechanism of miR-203 downregulation was closely associated with the hypermethylation in its promoter region.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Recently, hypermethylation of miR-203 promoter has been found in HCC, cervical cancer and CML [12,13,17,32]. In this study, we confirmed that the mechanism of miR-203 downregulation was closely associated with the hypermethylation in its promoter region.…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies found that miR-203 was significantly deregulated in cervical carcinoma [11,12,13]; however, the underlying mechanisms by which miR-203 affects tumor growth and angiogenesis are still not well elucidated. In the present study, we confirmed that miR-203 expression levels were significantly down-regulated in cervical cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in cervical cancers has been linked to increased promoter methylation of respective genes 73,74,83,84 . These data are fully in line with the concept that an increase in specific genetic and epigenetic alterations reflects a longer duration of existence of the underlying lesion.…”
Section: Mir-124-2 Hsa-mir-124-3 Hsa-mir-149 Hsa-mir-203 Hsa-mir-mentioning
confidence: 99%
“…MiR-149C>T polymorphisms have been widely investigated in various cancers, such as gastric cancer, lung cancer, colorectal cancer, nasopharyngeal carcinoma, and breast cancer (Luo et al, 2012;Wang et al, 2012;Øster et al, 2013;Wilting et al, 2013;Zhang et al, 2013). Two studies reported that miRNA-149C>T polymorphisms are associated with the development of HCC (Liu et al, 2010;Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%